2021
DOI: 10.3390/cells10092474
|View full text |Cite
|
Sign up to set email alerts
|

P-Rex1 Controls Sphingosine 1-Phosphate Receptor Signalling, Morphology, and Cell-Cycle Progression in Neuronal Cells

Abstract: P-Rex1 is a guanine-nucleotide exchange factor (GEF) that activates Rac-type small G proteins in response to the stimulation of a range of receptors, particularly G protein-coupled receptors (GPCRs), to control cytoskeletal dynamics and other Rac-dependent cell responses. P-Rex1 is mainly expressed in leukocytes and neurons. Whereas its roles in leukocytes have been studied extensively, relatively little is known about its functions in neurons. Here, we used CRISPR/Cas9-mediated P-Rex1 deficiency in neuronal P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…PC12 rat phaeochromocytoma cells were a kind gift from Dr Llewelyn Roderick, Babraham Institute, Cambridge, UK. From these, we derived PC12-S1PR1 cells which stably express C-terminally GFP-tagged S1PR1, as described previously 28 . Cells were maintained in complete Dulbecco’s Modified Eagle’s Medium (DMEM, Gibco, 41,965–039), supplemented with 10% horse serum, 5% foetal bovine serum, 1 U/ml penicillin and 1 U/ml streptomycin (Gibco, 15,140–122), 2 mM glutamine, and 500 µg/ml G-418 disulphate (Melford, Ipswich, UK, G0175)) in poly-D-lysine coated vented tissue culture flasks (Nunc) at 37 °C in a humidified, 5% CO 2 incubator.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…PC12 rat phaeochromocytoma cells were a kind gift from Dr Llewelyn Roderick, Babraham Institute, Cambridge, UK. From these, we derived PC12-S1PR1 cells which stably express C-terminally GFP-tagged S1PR1, as described previously 28 . Cells were maintained in complete Dulbecco’s Modified Eagle’s Medium (DMEM, Gibco, 41,965–039), supplemented with 10% horse serum, 5% foetal bovine serum, 1 U/ml penicillin and 1 U/ml streptomycin (Gibco, 15,140–122), 2 mM glutamine, and 500 µg/ml G-418 disulphate (Melford, Ipswich, UK, G0175)) in poly-D-lysine coated vented tissue culture flasks (Nunc) at 37 °C in a humidified, 5% CO 2 incubator.…”
Section: Methodsmentioning
confidence: 99%
“…PC12-S1PR1 cells were transfected with this sgRNA and with a GeneArt CRISPR Nuclease Vector that expresses orange fluorescent protein (OFP) (Thermo Fisher Scientific, A21174) using JetPEI transfection reagent (Polyplus 101-10N), following the manufacturer’s protocol. 44 h later, the cells were resuspended in DMEM, 1% FBS, 2 mM glutamine, and OFP-positive cells were enriched by fluorescence-activated cell sorting as described 28 . Single cells were sorted into 96-well plates and cultured for clonal expansion in the complete growth medium.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Kristensson reviewed the GTP-binding domains of α-, β-, and γ-tubulin and elaborated on the functions of the γ-tubulin GTP-binding domain in the regulation of the γ-tubulin meshwork dynamics and cellular homeostasis [ 5 ]. In the only original research paper in the collection, Hampson and colleagues revealed the role of P-Rex1, a GEF that activates Rac small GTPases in response to G-protein-coupled receptors (GPCR) activation, in sphingosine 1-phosphate (S1P) signaling [ 6 ]. The authors showed, using PC12 cells that stably overexpressed the S1P receptor, that P-Rex1 is required for the S1P-stimulated activation of Rac1 and Akt.…”
mentioning
confidence: 99%